A Taste of Capsicum: Practical Capabilities for UNIX. (Communications of the ACM, 2012)
Capsicum is a lightweight operating system (OS) capability and sandbox framework planned for inclusion in FreeBSD 9. Capsicum extends, rather than replaces, UNIX APIs, providing new kernel primitives (sandboxed capability mode and capabilities) and a userspace sandbox API. These tools support decomposition of monolithic UNIX applications into compartmentalized logical applications, an increasingly common goal that is supported poorly by existing OS access control primitives. We demonstrate our approach by adapting core FreeBSD utilities and Google’s Chromium Web browser to use Capsicum primitives, and compare the complexity and robustness of Capsicum with other sandboxing techniques.